A NARRATIVE REVIEW ON DEFINING AGING: A MULTIDISCIPLINARY REVIEW OF BIOLOGICAL, PSYCHOLOGICAL, SOCIOLOGICAL, AND CLINICAL PERSPECTIVES WITH A FOCUS ON SUCCESSFUL AGING. - Singh, D P; Singh, Vijay Krishna (Student's Journal of Health Research Africa, 2024)
Aging is a complex, multifaceted process affecting every living organism, characterized by progressive physiological changes, functional decline, and increased susceptibility to diseases and death. As the global population continues to age, understanding and defining aging becomes increasingly important for healthcare, policy-making, and social support systems. The review aims to explore and synthesize various definitions of aging, including biological, psychological, sociological, and clinical perspectives, and to examine the concept of successful aging. The review identifies distinct definitions of aging across different disciplines, highlighting the multifaceted nature of the idea. Biological aging involves cellular senescence, genetic theories, and damage accumulation. Psychological aging encompasses cognitive changes and emotional regulation, while sociological aging focuses on social roles and cultural attitudes. Clinical aging addresses the decline in physical and mental health and the emergence of geriatric syndromes. The maintenance of physical health, mental well-being, social engagement, and productive activities defines successful aging. Factors influencing successful aging include genetics, lifestyle choices, social support, and access to healthcare. Understanding the various definitions of aging is crucial for advancing research, developing effective interventions, and shaping policies that support healthy aging. Future research should explore the interplay between genetic, environmental, and social determinants of aging, and promote societal attitudes that value and support older adults. Insights from this review can inform the design of clinical programs and policies aimed at enhancing the quality of life for older adults. Emphasizing preventive measures, health promotion, and social support can help mitigate the negative impacts of aging and promote successful aging across populations.